The impact of firm entry regulation on long-living entrants - Susanne Prantl (Max Planck Institute for Research on Collective Goods, 2010)
What is the impact of firm entry regulation on sustained entry into self-employment? How does firm entry regulation influence the performance of long-living entrants? In this paper, I address these questions by exploiting a natural experiment in firm entry regulation. After German reunification, East and West Germany faced different economic conditions, but fell under the same law that imposes a substantial mandatory standard on entrepreneurs who want to start a legally independent firm in one of the regulated occupations. The empirical results suggest that the entry regulation suppresses long-living entrants, not only entrants in general or transient, short-lived entrants. This effect on the number of long-living entrants is not accompanied by a counteracting effect on the performance of long-living entrants, as measured by firm size several years after entry.
Keywords: K20; L25; L26; L50; M13; P52; 330; firm entry regulation; sustained entry; self-employment; firm size; Markteintritt; Regulierung; Unternehmensgründung; Selbstständige; Unternehmensentwicklung; Betriebsgröße; Gewerberecht; Deutschland